(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The importance of viewing theatre from a socio-cultural perspective is examined in this essay. It makes the case that analysing performers in light of their historical and cultural backgrounds discloses power relations, opens up formerly undiscovered tiers, and encourages vital ideas about what it means to be human. The essay presents essential theoretical stances, consisting of postcolonialism, feminism, and Marxism, and suggests how they might be used to shed light on the intricacies of dramatic tales. The study illustrates how language, narrative, location, and personal improvement replicate and affect social issues, electricity systems, and cultural identities through careful readings of positive performances. The research emphasises the necessity for accountable and nuanced techniques, acknowledging the problems of ancient distance, simplicity, and possible biases in socio-cultural interpretations. The review concludes with recommendations for future research projects. It promotes the usage of digital technology, global viewpoints, intersectional frameworks, and multidisciplinary conversations to further our understanding of theatre within its complicated socio-cultural context.